Unit Linked Insurance Plans - The Taster's Perceptions on The Mixed Bag of Fruits - Chandra Prasad, J.; Hari Babu, S.; Chiranjeevi, K.; Visweswara Rao, K. V. V. S. (Indian Journal of Finance, 2009)
Unit Liked insurance policy1 is a unique, multiple benefits plan which combines the basic benefit of life insurance, tax benefits, accident insurance cover and growth prospects. It is a life insurance solution that provides for the benefits of protection and flexibility in investment. ULIPs have gained high acceptance due to attractive features they offer.